Influence of psychological distance between family members on teenager's motivation for studying - Suleymanov, Ramil F.; Gorenkov, Roman V.; Kolosova, Olga A.; Molodozhnikova, Natalia M. (Opción, 2020)
The objectives of the study are to identify the type of the relationship between students and their parents and its influence on academic performance; based on the result analysis, formulate a problem (problems) and suggest possible solutions. The results showed that students who have stronger ties with their parents are generally more motivated to study and demonstrate better academic performance than those who distance themselves from their families. The lack of attachment between parents and children can be a serious problem in adolescence life when mental health is being restructured.